Advertising & IMC: Principles and Practice, Global Edition - Moriarty, Sandra; Mitchell, Nancy; Wood, Charles; Wells, William D. (Pearson International Content, 2018)
The full text downloaded to your computer With eBooks you can: search for key concepts, words and phrases make highlights and notes as you study share your notes with friends eBooks are downloaded to your computer and accessible either offline through the Bookshelf (available as a free download), available online and also via the iPad and Android apps. Upon purchase, you'll gain instant access to this eBook. Time limit The eBooks products do not have an expiry date. You will continue to access your digital ebook products whilst you have your Bookshelf installed. For courses in introductory advertising.   Increase the relevancy and effectiveness of marketing communications Advertising & IMC: Principles and Practice presents the strategic use of communications to engage different types of consumers. Covering advertising, public relations, direct marketing, promotion, and more, Advertising & IMC uses examples of award-winning brand campaigns, contributions from experts, and enduring principles and practices to provide students with a practical guide to executing integrated marketing communications.   And with a new author joining the team, the 11th Edition features a significant reorganisation and revision of the material. Now, readers will understand not only the types of marketing communication possible, but also their application of strategy and planning, and how these areas work together — ensuring students are prepared to deal with the latest industry practices in their future careers.